2019
DOI: 10.1029/2018jd029707
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Convective Systems in the Asian Monsoon Region From Advanced Himawari Imager: Algorithms and Preliminary Results

Abstract: The knowledge of mesoscale convective system (MCS) in the Asian monsoon region remains still deficient due to the limited available data and less powerful algorithms. Here, using the data from Advanced Himawari Imager onboard Himawari‐8 (HW8), an improved algorithm combining the area overlapping with the Kalman filter is developed, which captures much smaller MCSs that are unavailable otherwise. Several influential factors like the overlapping rate and splitting/merging in the area overlapping method, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 87 publications
(149 reference statements)
4
59
1
Order By: Relevance
“…A comprehensive study of zonal distributions and life cycles of MCSs over China with a special focus on the classification of MCSs into different morphologies (e.g., quasi-circular MCSs and elongated MCSs), has been conducted based on brightness temperature data from the geostationary satellite Fengyun 2 (Yang et al 2015). Chen et al (2019) have shown the preliminary results of MCS major features (including horizontal movement and frequency of occurrence) in the whole of East Asia, by investigating a 1-yrlong dataset from Advanced Himawari Imager onboard Himawari-8. Other studies have also documented organizational modes (Zheng et al 2013), life cycle characteristics (Ai et al 2016), formation mechanisms (Fu et al 2017) of MCSs, and the associated atmospheric circulation patterns (He et al 2017) over the plain region of central-eastern China.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive study of zonal distributions and life cycles of MCSs over China with a special focus on the classification of MCSs into different morphologies (e.g., quasi-circular MCSs and elongated MCSs), has been conducted based on brightness temperature data from the geostationary satellite Fengyun 2 (Yang et al 2015). Chen et al (2019) have shown the preliminary results of MCS major features (including horizontal movement and frequency of occurrence) in the whole of East Asia, by investigating a 1-yrlong dataset from Advanced Himawari Imager onboard Himawari-8. Other studies have also documented organizational modes (Zheng et al 2013), life cycle characteristics (Ai et al 2016), formation mechanisms (Fu et al 2017) of MCSs, and the associated atmospheric circulation patterns (He et al 2017) over the plain region of central-eastern China.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…MCSs can be identified and tracked by multiple atmospheric fields, including but not limited to cloud-related variables such as cloud-top brightness temperature derived from satellite infrared images (Yang et al 2015;Chen et al 2019;Q. Yang et al 2019), midtropospheric vorticity (Wang et al 2011), Doppler radar composite reflectivity (Zheng et al 2013), and surface precipitation (Houze 2004Clark et al 2014;Prein et al 2017a,b).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, passive sensor can only measure information on the cloud surface (Chen et al, 2019). Even if the vertical evolution of R e can be obtained through appropriate assumptions, the structure at low level is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of new‐generation geostationary meteorological satellite makes it possible to identify the life cycle of clouds in Asian monsoon regions (Chen et al, ). This may lead to a major leap in our understanding of the aerosol impact on cloud lifetimes, which is the least understood aerosol‐cloud‐interaction process.…”
Section: Concluding Remarks Problems and Future Directionsmentioning
confidence: 99%